Cyber-Routines, Political Attitudes, and Exposure to Violence-Advocating Online Extremism. (12th December 2018) - Hawdon, James; Bernatzky, Colin; Costello, Matthew
Abstract: The Internet's relatively unfettered transmission of information risks exposing individuals to extremist content. Using online survey data ( N = 768) of American youth and young adults, we examine factors that bring individuals into contact with online material advocating violence. Combining aspects of social structure-social learning theory with insights from routine activity theory, we find that exposure to violence-advocating materials is positively correlated with online behaviors, including the use of social media platforms and the virtual spaces individuals frequent. Target antagonism is also correlated with exposure to violence-advocating materials, but guardianship and online and offline associations are not. Finally, feelings of dissatisfaction with major social institutions and economic disengagement are associated with exposure to violent materials online.